Pengaruh Fasilitas Olahraga Terhadap Kepuasan Pelanggan Member Sport Club Meadow Terrace BSD - Akbar, Mada Faisal; Ariyanto, Aris; Sudarsono, Agus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The research objective was to determine the facilities and customer satisfaction at Sport Club Meadow Terrace and the effect of facility satisfaction on customer satisfaction at Sport Club Meadow Terrace. This research is associative with a quantitative approach. The population in this study were all members of the Meadow Terrace Sport Club from 2018 to 2020, namely 143 people, while the sample used in the study used a saturated sampling technique, where all the populations were made respondents. Data collection techniques by means of questionnaires, and data analysis techniques using test instruments, classical assumption tests, regression analysis, coefficient of determination, t-test and f-test. The results showed that the Facility variable (X) which consisted of 10 (ten) instruments showed that the total score was 6105 and the average score was 4.27 and entered into the interval with the Good category, so it can be concluded that, Facility (X) when this is going well. Based on the distribution of the answers to the satisfaction variable (Y) which consists of 8 (eight) instruments, it shows that the total score is 4597 and the average score is 4.02 and it is included in the interval with the Good category, it can be concluded that, at this time, satisfaction (Y) is going well. Based on data analysis, it shows that there is a positive and significant effect of facilities (X) on customer satisfaction (Y) sport club meadow terrace. The simple regression equation Y = a + b (x) is Y = 15,597 = 0.388x this equation can be concluded that there is a direction of positive influence between the facility variable (X) on the satisfaction variable (Y)